2013
DOI: 10.1007/s00520-013-1934-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study of treatment pattern, effectiveness and safety of zoledronic acid therapy beyond 24 months in patients with multiple myeloma or bone metastases from solid tumors

Abstract: Beyond 2 years of therapy, treatment patterns of ZOL were heterogeneous and SRE rates were low. The safety profile of ZOL was acceptable, and interrupting ZOL in patients with solid tumors was associated with a higher risk of SREs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…For example, studies showed that persistent, monthly use of BPs for more than 18 months was associated with a 50% lower risk of SREs compared with persistent, monthly use of BPs for less than 3 months in breast cancer patients with bone metastases [ 28 ]. In addition, even for patients with solid tumors who already received BP treatment for at least 2 years, the persistent use of BPs for an additional 18 months was associated with a lower SRE risk (hazard ratio = 0.42, P = 0.01) [ 29 ]. Our survey also showed that the persistent use of BPs for more than 6 months could significantly prolong the time to the first SRE compared with the use of BPs for less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies showed that persistent, monthly use of BPs for more than 18 months was associated with a 50% lower risk of SREs compared with persistent, monthly use of BPs for less than 3 months in breast cancer patients with bone metastases [ 28 ]. In addition, even for patients with solid tumors who already received BP treatment for at least 2 years, the persistent use of BPs for an additional 18 months was associated with a lower SRE risk (hazard ratio = 0.42, P = 0.01) [ 29 ]. Our survey also showed that the persistent use of BPs for more than 6 months could significantly prolong the time to the first SRE compared with the use of BPs for less than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate (BP), an antiresorptive drug, acts as osteoclast function inhibitor which is led to decrease bone remodeling. [ 3 ] BP is effective against several conditions such as hypercalcemia of malignancy, multiple myeloma, and osteoporosis[ 4 5 ] in addition to skeletal-related events associated with metastatic bone disease along with solid tumors such as prostate, breast, lung cancers, and renal cell carcinoma. [ 6 ] The oral form of BP is used to treat osteoporosis, osteogenesis imperfecta, osteopenia in addition to Paget’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] Intravenous (IV) bisphosphonates (BPs) are used in the treatment of cancer-related conditions as well as skeletal-related events associated with bone metastases, hypercalcemia of malignancy, and for the management of lytic lesion in the setting of multiple myeloma. [ 3 4 5 ] Oral BPs are used to manage condition including osteoporosis,[ 6 ] osteopenia,[ 7 ] osteogenesis imperfecta,[ 8 ] and Paget's disease. [ 9 ] RANK ligand inhibitor (denosumab) is an antiresorptive drug, which arrests the function of osteoclasts, reduces bone resorption, and intensifies bone density.…”
Section: Introductionmentioning
confidence: 99%